Formulation of Chitin-glucan complex and FucoPol biopolymers particles for controlled release of fertilizers - Nóbrega, Sónia Rodrigues (2017)
The development of controlled release fertilizers (CRFs) as increased interest for the agriculture sector, in order to turn it in a more sustainable activity, diminishing nutrient losses and increasing crop productivities. The CRFs properties are improved with the use of coatings, which is mostly performed using synthetic polymers, but since they are not biodegradable causing an additional environmental concern. In order to overcome this issue synthetic problems may be substituted by biopolymers, which are biodegradable and non-toxic like chitin-glucan complex and FucoPol. The main goal of this work was to produce nitrogen containing particles from two microbial biopolymers, chitin-glucan complex (CGC) and FucoPol. Therefore, ammonium nitrate was adsorbed to CGC particles at 15 g L-1 by submitting them to a saturated solution. There was a nitrogen uptake of 22.55 %, in 2 h contact, at pH 5.0. Hydrogel particles were produced from a FucoPol 10 g L -1 solution dissolved in 15 and 30 g L-1 of ammonium nitrate, and dropped in iron (III) chloride hexahydrate solution. The nitrogen uptake was 0.34 g L-1 and 0.53 g L-1, respectively. The nitrogen particles release was tested in water and soil. For the nitrogen CGC particles in water at 25 ºC, a burst release was verified for ammonium (NH4+) and nitrate (NO3-) in the initial two days assay and in soil, the same happened in the initial five days assay. To the nitrogen FucoPol particles in water was observed a burst release for ammonium and nitrate in the first day and in soil in two days. The water is an extremer medium than soil, which would potentiate the burst release of the nutrients from the particles. Lastly, the nitrogen biopolymer particles were evaluated in the germination and growth of pea (Pisum sativum) seeds. For the tests with nitrogen FucoPol particles as fertilizer it was verified a good germination and fast growth. Tests with nitrogen CGC particles presented a slower germination and growth. Therefore, nitrogen FucoPol particles have potential to be used in controlled release of nutrients.